ALIH KODE DAN CAMPUR KODE DALAM NOVEL FAITH AND THE CITY KARYA HANUM SALSABIELA RAIS DAN RANGGA ALMAHENDRA - Qutratuain, Saskia; Mayong, Mayong; Faisal, Faisal (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2022)
This study aims to describe the types and factors causing code switching and code mixing in the novel Faith and the City by Hanum Salsabiela Rais and Rangga Almahendra. This type of research is descriptive qualitative. According to results, there are three types of code mixing found are insertion, alternation, and congruent lexicalization types. The factors of code mixing are talking about certain topics, citing other people's conversations, emphasizing something, exclamations, repetition to clarify, clarifying the contents of the conversation to others. interlocutor, shows the identity of a group, expands or emphasizes requests or orders, lexical needs, and the efficiency of a conversation.